2017
DOI: 10.1542/peds.2016-3432
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bronchiolitis Clinical Pathway Adherence With Length of Stay and Costs

Abstract: High adherence to bronchiolitis clinical pathway recommendations across care settings was associated with shorter LOS and lower cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 24 publications
4
44
3
3
Order By: Relevance
“…(35) More recently, a retrospective study showed how adherence to a standardized clinical pathway in 267 children with bronchiolitis was associated with shorter length of stay in the emergency department (ED), with no significant differences in hospital stay. (36) Contrary to those studies, we found that the implementation of a discharge protocol significantly reduced length of stay with no increase in readmission rates. These discrepancies may be related to differences in the populations included and study design, since thresholds to discontinue supplemental oxygen, acceptable duration without oxygen therapy or admissible oral intake at discharge were not homogeneous or completely addressed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…(35) More recently, a retrospective study showed how adherence to a standardized clinical pathway in 267 children with bronchiolitis was associated with shorter length of stay in the emergency department (ED), with no significant differences in hospital stay. (36) Contrary to those studies, we found that the implementation of a discharge protocol significantly reduced length of stay with no increase in readmission rates. These discrepancies may be related to differences in the populations included and study design, since thresholds to discontinue supplemental oxygen, acceptable duration without oxygen therapy or admissible oral intake at discharge were not homogeneous or completely addressed.…”
Section: Discussioncontrasting
confidence: 99%
“…Utilization of these pathways have been associated with a reduction on resource utilization (chest-x rays, albuterol or steroid use) with variable results in terms of clinical outcomes. (3436, 3840) A study comparing a cohort of 229 infants with bronchiolitis who were managed based on a clinical pathway, with a historical cohort of 207 children managed without the pathway, showed that protocol adherence was associated with decreased readmission rates with no impact on length of hospital stay. (35) More recently, a retrospective study showed how adherence to a standardized clinical pathway in 267 children with bronchiolitis was associated with shorter length of stay in the emergency department (ED), with no significant differences in hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the clinical pathway of the pediatric DHF treatment in the studied hospital was fairly well-implemented. This result corresponds to previous research (Bryan et al, 2017), which confirmed that the number of patients who receive treatments adhering to clinical pathways is significantly higher than in the opposite group.…”
Section: Conformity Of Pediatric Dhf Treatments To the Clinical Pathwaysupporting
confidence: 91%
“…In studies of other pediatric diseases such as bronchiolitis, differences in LOS of less than 1 day have been reported as clinically important given their association with decreased costs. 39 Additionally, when comparing those patients that demonstrated the longest lengths of stay (those above the 75 th percentile), there appear to be more clinically meaningful differences among patients from different races, particularly among hospitalizations of patients with CD.…”
Section: Discussionmentioning
confidence: 99%